Pengaruh Kesetaraan Gender terhadap Ketimpangan Capaian Pendidikan di Indonesia Tahun 2015–2019 - Yuniar, Aninditya; Yuniasih, Aisyah Fitri (Jurnal Ekonomi dan Pembangunan Indonesia, 2022)
Education is one of the most fundamental of human capital. The right to education is written in UUD 1945 and policy of compulsory education has already been implemented, yet the mean years of schooling in Indonesia is still low. It is assumed that there is education inequality. Method of analysis used in this research is panel data regression model FEM with FGLS–SUR. The research finds that education inequality in Indonesia is classified as low inequality in the past 5 years and is effected significantly by gender equality, government budget, unemployment rate, and Gini ratio.